Prevalence and natural development of thoracolumbar kyphosis in achondroplasia: A systematic review and meta-analysis - Chady Omara; Rania A. Mekary; Carmen L.A. Vleggeert-Lankamp (Brain and Spine)
Introduction: Thoracolumbar kyphosis (TLK) is a frequently reported spinal deformity in achondroplasia, which in combination with the characteristic narrow spinal canal in achondroplasia predisposes for symptomatic spinal stenosis. There is however no consensus on the optimal treatment, due to limited data on diagnostic criteria, the natural development and the prevalence of TLK. Research question: This study aims to assess the prevalence, natural development, and diagnostic criteria for pathological TLK in individuals with achondroplasia. Material and methods: A systematic review and meta-analysis were conducted. Studies involving achondroplasia patients, which reported TLK measurement methods were included. The primary outcome was the pooled prevalence of TLK, stratified by age. Results: Eight studies, encompassing 852 patients, met the inclusion criteria. Pathological TLK was most frequently defined as a Cobb angle of 20° or greater, between T10 and L2. TLK was present in 87% (95% CI 80%–91%) of patients under two years old, decreasing to 33% (24%–43%) at age three, 26% (19%–35%) between five and ten years, and 23% (16%–31%) in patients aged 10–20 years. Discussion and conclusion: Pathological TLK in achondroplasia, defined as a Cobb angle of 20° or greater, appears primarily in early childhood and often resolves by walking age. However, approximately one-fourth of cases persist into adulthood, with factors such as developmental motor delay and vertebral wedging contributing to this persistence. Routine clinical and radiological evaluations during childhood, along with conservative management, are recommended to mitigate the need for surgery during adulthood.